2020
DOI: 10.1101/2020.03.11.987545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological profiling of tubercule bacilli identifies drug pathways of action

Abstract: 34 35 36 Keywords 37 tuberculosis, drug discovery, cell morphology, high throughput 38 39 40 41 42 43 2 Abstract 44Morphological profiling is a method to classify target pathways of antibacterials based on how 45 bacteria respond to treatment through changes to cellular shape and spatial organization. Here, we utilized 46 the cell-to-cell variation in morphological features of Mycobacterium tuberculosis bacilli to develop a rapid 47 profiling platform called Morphological Evaluation and Understanding of Stress… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Mycobacteria, including Mtb , demonstrate morphological and metabolic plasticity in response to environmental and antibiotic stresses ( 16 18 ). We reasoned that if Mtb bacilli were exposed to antibiotics before aerosolization, a discernible change in bacterial morphology and/or metabolic state might be detectable between treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…Mycobacteria, including Mtb , demonstrate morphological and metabolic plasticity in response to environmental and antibiotic stresses ( 16 18 ). We reasoned that if Mtb bacilli were exposed to antibiotics before aerosolization, a discernible change in bacterial morphology and/or metabolic state might be detectable between treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…In replicating Mtb pretomanid has been shown to act in part by inhibiting the biosynthesis of essential mycolic acids (Stover et al, 2000). Although bedaquiline is an ATP synthesis inhibitor, we and others have shown that the resulting downstream metabolic perturbation produces morphological changes that resemble those from cell wall-acting inhibitors (Mackenzie et al, 2020;Smith et al, 2020).…”
Section: Articlementioning
confidence: 80%
“…Compound-treated Mtb cultures were fixed with 4% paraformaldehyde (Alfa Aesar, 43368) for 1 h, washed twice with 100 mL PBS containing 0.2% Tween 80 (PBST), and resuspended in 100 mL PBST. Staining and imaging were as described previously (Smith et al, 2020). In brief, 50 mL of fixed Mtb cells was diluted with 50 mL PBST and stained with 0.6 mg of FM4-64-FX (Thermo Fisher Scientific; F34653) and 15 mL of 0.1 mM SYTO 24 (Thermo Fisher Scientific; S7559) at room temperature in the dark for 30 min.…”
Section: Morpheus Analysismentioning
confidence: 99%
See 2 more Smart Citations